1997
DOI: 10.1039/a703762g
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric and spectroscopic study of copper(II) and nickel(II) complexes of trans-dioxopentaaza macrocycles in aqueous solution

Abstract: The trans-dioxopentaaza macrocycles 2,6-dioxo-1,4,7,10,13-pentaazacyclopentadecane (L 1 ) and 2,6-dioxo-1,4,7,11,14-pentaazacycloheptadecane (L 2 ) have been prepared. Their protonation and metal-binding properties with Cu 2ϩ and Ni 2ϩ have been investigated in 0.10 mol dm Ϫ3 KNO 3 (aq) at 25.0 ЊC by potentiometric pH-metry, calorimetry (in part), electronic absorption and IR spectroscopy. Metal-ion complexation promotes the deprotonation and the co-ordination of the amide nitrogens, resulting in neutral compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…From the same method, the carbonate content of the strong base which can interfere in further experiments can be calculated. 24…”
Section: Experimental Potentiometric Titrationsmentioning
confidence: 99%
“…From the same method, the carbonate content of the strong base which can interfere in further experiments can be calculated. 24…”
Section: Experimental Potentiometric Titrationsmentioning
confidence: 99%
“…et al 14 have recently observed a similar electron withdrawing property of an amide group in the dioxomacrocylic analogues of L a . The benzylamine is also 2-4 log units more basic than the central amine of L 1 -L 4 (Fig.…”
Section: Protonation Constantsmentioning
confidence: 62%
“…However, this behaviour was not observed for the previously studied N,N -bis(2-hydroxyiminopropionyl) propane-1,3-diamine ligand reported 2 by us, nor for dioxocyclomacrocycles, 2,6-dioxo-1,4,7,10,13-pentaazacyclopentadecane and 2,6-dioxo-1,4,7,11,14pentaazacycloheptadecane, investigated by Steenland and coworkers. 14 In contrast to the earlier syntheses of related ligand systems, 7 the compound L a was obtained in a mono-hydrochloride form (C 21 H 38 N 5 O 2 Cl) as a pure diastereoisomer suitable for analysis and potentiometric titrations. The presence of the mono-protonated ligand was revealed by an m/z signal centred at 392.54259 [HL a ] + (C 21 H 38 N 5 O 2 ).…”
Section: Ligand Synthesismentioning
confidence: 99%
“…Jackson et al reported p K a 1 and p K a 2 values for N,N′-bis[aminoethyl] ethanediamne, that is, H 2 N-CH 2 -CH 2 -NH-C(O)-C(O)-NH-CH 2 -CH 2 -NH 2 , (p K a 1 = 9.31 and p K a 2 = 8.43) and N,N′-bis[2-(dimethylamino)-ethyl] ethanediamide, that is, Me 2 N-CH 2 -CH 2 -NH-C(O)-C(O)-NH-CH 2 -CH 2 -NMe 2 , (p K a 1 = 8.72 and p K a 2 = 7.92) [ 12 ]. The low value of the third protonation constant (p K a 3 = log⁡ β 013 − log⁡ β 012 ) of 2.03, 1.74, and 1.98 corresponding to the central pyridyl nitrogen for L1, L2, and L3, respectively, is due to the electronic repulsion effect and the base weakening effect of the adjacent amide groups [ 13 ]. Therefore, it is expected that the protonation constant corresponding to the central pyridyl nitrogen in L1, L2, and L3 should decrease further when two amide groups are present.…”
Section: Resultsmentioning
confidence: 99%